Engineering Critical Thinking in Chemical Engineering-Implementation and Student’s Perception (Jurnal Pendidikan IPA Indonesia, 2022)
Chemistry for Engineers is a fundamental subject in the Chemical Engineering curriculum, and it serves as a bridge between science and engineering by integrating theoretical concepts with real-world situations. To be successful in their careers, future engineers must master the skill of critical thinking. The goal of this research is to use the DoIt@Home Laboratory to improve students' critical thinking and problem-solving skills. The Carona pandemic necessitated the development of this component, which consists of a series of laboratory exercises that require pupils to demonstrate critical thinking skills. In order to better understand students' perceptions of and performance in learning CT skills using the new approach, surveys were utilized to evaluate the DoIt@Home Laboratory. We were able to demonstrate that the DoIt@Home Laboratory is an effective method for enhancing critical thinking skills. 75 % of students have adequate reasoning, evaluation, and problem-solving skills. Indicators from both chemistry and statistics lend credence to their arguments. 52 % of students think they have a good grasp on the fundamentals of chemistry, meaning that they can explain phenomena and study results, defend their positions with evidence, and synthesize arguments.